2020
DOI: 10.1007/s11004-020-09877-y
|View full text |Cite
|
Sign up to set email alerts
|

Is Cell-to-Cell Scale Variability Necessary in Reservoir Models?

Abstract: Reservoir models typically contain hundreds-of-thousands to millions of grid cells in which petrophysical properties such as porosity and permeability vary on a cell-to-cell basis. However, although the petrophysical properties of rocks do vary on a point-to-point basis, this variability is not equivalent to the cell-to-cell variations in models. We investigate the impact of removing cell-to-cell variability on predictions of fluid flow in reservoir models. We remove cell-to-cell variability from models contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…If heterogeneity exists within these volumes, they are further subdivided by additional surfaces. In these geologically meaningful domains, no further property modelling is required [1,2]. The application of NURBS provides a computationally efficient representation as few control points are required to represent even complex curves and surfaces.…”
Section: Nurbs For Generating Computationally Efficient Sbgmsmentioning
confidence: 99%
See 2 more Smart Citations
“…If heterogeneity exists within these volumes, they are further subdivided by additional surfaces. In these geologically meaningful domains, no further property modelling is required [1,2]. The application of NURBS provides a computationally efficient representation as few control points are required to represent even complex curves and surfaces.…”
Section: Nurbs For Generating Computationally Efficient Sbgmsmentioning
confidence: 99%
“…General trends and similarities with the reference data cannot be observed at well locations However, compared to other methods, the use of parametric, grid-free surface-based models for representing geological heterogeneity of interest such as features which influence the flow conditions has many advantages which outweigh any anticipated computational limitations. Furthermore, the number of surfaces required to model realistic reservoirs using surfaces has been shown by [2] to be low to generate representative models. 2.…”
Section: Uncertainty Assessment: Evaluating Spatial Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) which are efficient to construct and manipulate and are widely used in other areas of computer-aided-design (CAD) (Jacquemyn et al, 2019). NURBS surfaces are created automatically and probabilistically by placing control points at specific locations in space to create geologically meaningful geometries (Zhang and Pyrcz, 2006;Jacquemyn et al, 2019;Osman et al, 2020). Multiple surfaces can be created rapidly, and the geometry of each can be varied stochastically based on statistical data describing key aspects of the geometry.…”
Section: Surfaced-based Reservoir Modellingmentioning
confidence: 99%
“…Here, we identify the domains based on geology, rather than using an arbitrary mesh. It has been shown that capturing correlated variability using such geologically-defined domains is key for capturing flow (Osman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%